Оrgаnizing Science Lessоns Bаsed оn the Inquiry-Bаsed 5E Mоdel - Bаrnо Аbdulhаqоvnа Аmirullаyevа (International Journal on Integrated Education, 2024)
This article explores the implementation of the 5E inquiry-based teaching model to enhance science lessons, focusing on engaging students actively in learning through exploration, experimentation, and reflection. The study uses a structured approach based on cognitive psychology and constructivist learning theory to guide teachers in applying the 5E model's phases: Engage, Explore, Explain, Elaborate, and Evaluate. Teachers participated in professional development courses to strengthen their lesson-planning skills for inquiry-based education. The results show that the 5E model effectively improves students' scientific understanding and promotes higher engagement by aligning lessons with students’ interests and prior knowledge. Findings support the integration of inquiry-based learning as a core method in science education reforms, advocating for further training to improve instructional quality. This research underscores the potential of the 5E model to modernize science education, making it more interactive and student-centered.